Faktor-faktor yang Mempengaruhi terjadinya Nyeri Leher pada Pengguna Laptop - Lestari, Bekti; , Umi Budi Rahayu, S.Fis.,Ftr.,M.Kes; , Wahyuni, S.Fis.,Ftr.,M.Kes (2015)
Background: Musculoskeletal pain is pain in the neck which include neurological disorders, tendons, muscles and ligaments around the neck. Different types of work can lead to neck pain, especially during working with the wrong body position so as to make the neck are in a certain position for a long time, for example, workers who sit all day just to work with computers. Objective: To determine the factors that influence the occurrence of neck pain on the user's laptop. Methods: This study used a descriptive method with cross sectional approach. Samples were 100 respondents. To measure or determine the level of neck pain on respondents used a measuring tool that is Verbal Description Scale (VDS) in the form of words used to describe the level of pain ranging from mild to no pain unbearable pain. Analysis using chi square test which resulted in whether or not the relationship between the factors that influence the occurrence of neck pain on the user's laptop (independent variable) and neck pain. Results: The results showed that all variables have a value of p <0,05 so that Ho refused and Ha accepted, meaning that there is a relationship between the factors that affect the neck pain on the user's laptop. Conclusion: there is a relationship between the factors that influence the occurrence of neck pain on the user's laptop.